Total peace, a quest for peace between bilateral and multilateral - Chaverra Colorado, Fredy Alexánder (Revista Colombiana de Ciencias Sociales, 2026)
According to the implementation of the Total Peace policy, President Gustavo Petro (2022–2026) sought to differentiate himself from the partial peace policy pursued under the government of Juan Manuel Santos (2010–2018), who first negotiated between 2012 and 2016 with the Revolutionary Armed Forces of Colombia–People’s Army (FARC-EP) and later with the National Liberation Army (ELN)—signing an agenda agreement and a bilateral ceasefire—and also from the Peace with Legality policy of former President Iván Duque (2018–2022), who ultimately closed the door to dialogue with any armed group (Archila & Duque, 2021). At the outset, the Total Peace policy was embodied in Law 2272 of 2022 (Congress of the Republic of Colombia, 2022) as President Petro’s commitment to removing all illegal armed groups from war through negotiation. It offered processes of political dialogue for those groups that continuously exercise violence in an organized way, with recognized or responsible command in various regions of the country. It even opened the door to collective submission to justice through unprecedented socio-legal dialogue spaces with groups not classified as insurgencies, which the law called organized armed structures of high-impact crime.